The diagnostic value of computed tomography in delayed complications after cochlear implantation. (1st February 2021) - Wolber, Philipp; Shabli, Sami; Anagiotos, Andreas; Moellenhoff, Kathrin; Schwarz, David; Lang-Roth, Ruth
Abstract: Background: Delayed complications after cochlear implant (CI) surgery can result in the need for revision surgery. Temporal bone computed tomography (tCT) is frequently used in the diagnostic work-up for these patients. Aims/objectives: We aimed to test for the value of tCT in delayed complications after CI surgery. Material and methods: Retrospective chart review including all patients with CI who were consecutively enrolled in our academic tertiary care centre and received a tCT due to delayed complications between January 2008 and December 2017. Results: A total of 85 patients with a mean age of 28 years at CI surgery were identified. Mean time between CI and tCT was 4.3 years. Reasons for performance of tCT were device malfunction (20%), cephalgia (20%), scalp hematoma/seroma (15.3%), device failure (11.8%), vertigo (10.6%), local infection (7.1%), trauma (5.9%), meningism (3.5%), tinnitus (3.5%) and facial palsy (2.4%). No abnormalities in tCT were detected in 82.4%. However, an abnormal tCT was a predictor for surgical therapy ( p  < .001). Conclusions and significance: We recommend the performance of tCT in CI patients with delayed complications to identify or rule out pathology in order to choose the most ideal and relevant individual treatment.